TaGW2L, a GW2-like RING finger E3 ligase, positively regulates heading date in common wheat (Triticum aestivum L.) - Daijing Zhang; Xiaoxu Zhang; Wu Xu; Tingting Hu; Jianhui Ma; Youfu Zhang; Jian Hou; Chenyang Hao; Xueyong Zhang; Tian Li (Crop Journal, 2022)
RING finger E3 ligases play an important role in regulating plant growth and development by mediating substrate degradation. In this study, we identified TaGW2L, encoding a Grain width and weight2 (GW2)-like RING finger E3 ligase, as a novel positive regulator of heading date in wheat (Triticum aestivum L.). TaGW2L exhibited high amino acid sequence similarities with TaGW2 homoeologs, particularly in the conserved RING finger domain. Expression analysis indicated that TaGW2L was constitutively expressed in various wheat tissues. TaGW2L showed transactivation activity in yeast and could interact with the ubiquitin-conjugating enzymes E2s. An in vitro ubiquitination assay verified that TaGW2L possessed a similar E3 ligase activity to TaGW2. Overexpression of the TaGW2L-7A homoeolog in wheat led to a significantly earlier heading date under both natural conditions and long-day conditions. Transcriptome analysis revealed that multiple known genes positively regulating wheat heading were significantly upregulated in the TaGW2L-7A-overexpression plants compared with the wild-type control. Together, our findings shed light on the role of TaGW2L in wheat heading date and provide potential applications of TaGW2L for the adaptation improvement of crops.